TRNA mutations that affect decoding fidelity deregulate development and the proteostasis network in zebrafish - Reverendo, Marisa (2020)
Mutations in genes that encode tRNAs, aminoacyl-tRNA syntheases, tRNA modifying enzymes and other tRNA interacting partners are associated with neuropathies, cancer, type-II diabetes and hearing loss, but how these mutations cause disease is unclear. We have hypothesized that levels of tRNA decoding error (mistranslation) that do not fully impair embryonic development can accelerate cell degeneration through proteome instability and saturation of the proteostasis network. To test this hypothesis we have induced mistranslation in zebrafish embryos using mutant tRNAs that misincorporate Serine (Ser) at various non-cognate codon sites. Embryo viability was affected and malformations were observed, but a significant proportion of embryos survived by activating the unfolded protein response (UPR), the ubiquitin proteasome pathway (UPP) and downregulating protein biosynthesis. Accumulation of reactive oxygen species (ROS), mitochondrial and nuclear DNA damage and disruption of the mitochondrial network, were also observed, suggesting that mistranslation had a strong negative impact on protein synthesis rate, ER and mitochondrial homeostasis. We postulate that mistranslation promotes gradual cellular degeneration and disease through protein aggregation, mitochondrial dysfunction and genome instability.